The lost boys of Barlowe Theater [large type] - Wright, Jaime Jo (Thorndike Press large print Christian fiction series., 2023)
"Barlowe Theater stole the life of Greta Mercy's brother during its construction. Now in 1915, the completed theater appears every bit as deadly. When Greta's younger brother goes missing after breaking into the building, Greta engages the assistance of a local police officer to help her uncover the already ghostly secrets of the theater. But when help comes from an unlikely source, Greta decides that to save her family she must put the threat of the phantoms to rest. Decades later, Kit Boyd's best friend vanishes during a ghost walk at the Barlowe Theater, and old stories of mysterious disappearances and ghoulish happenings are revived. When television ghost-hunting host and skeptic Evan Fisher engages Kit in the quest to identify the truth behind the theater's history, Kit reluctantly agrees to work with him in hopes of also finding out what happened to her friend. As the theater's curse begins to unravel Kit's own life, she sets out not only to save the historical building and her friend, but to end the pattern of evil that has marked their hometown for a century. In this atmospheric dual-time tale, two women--separated by a century yet bound by the ghosts of the past--pursue light in the face of darkness"--